Exploring Residential Models of Care for Treatment of Infectious Complications Among People Who Inject Drugs: a Systematic Review. - Saxton, Kaitlin G.; Barrett, David; Gould, Laurie; Sandieson, Rachel M.; Koivu, Sharon; Meyer, Matthew J. (International Journal of Mental Health & Addiction, 2020)
This article identifies, compares, and assesses residential models of care to treat infectious complications among people who inject drugs (PWID) through intravenous antibiotic (IV) therapy. Database searches in Ovid MEDLINE, Embase, PsycINFO, and the Cumulative Index to Nursing and Allied Health Literature Studies were performed. A Google web search was also performed. Studies published in English between 2000 and May 2017 that presented data on an out-of-hospital residential program for IV antibiotic treatment of infectious complications among PWID were included. Of the 2355 unique articles screened, 218 were reviewed in their entirety and three were included. Across the three included studies, no mortalities were reported during the study. Each study reported similar outcomes compared to in-hospital care. In the two studies reporting costs, residential care was substantially less expensive. This review indicates that residential treatment appears to be beneficial to PWID, hospitals, and the health care system.